Frequency of GJB2 mutations in patients with nonsyndromic hearing loss from an ethnically characterized Brazilian population - Felix,Felippe (2019)
Abstract Introduction: In different parts of the world, mutations in the GJB2 gene are associated with nonsyndromic hearing loss, and the homozygous 35delG mutation (p.Gly12Valfs*2) is a major cause of hereditary hearing loss. However, the 35delG mutation is not equally prevalent across ethnicities, making it important to study other mutations, especially in multiethnic countries such as Brazil. Objective: This study aimed to identify different mutations in the GJB2 gene in patients with severe to profound nonsyndromic sensorineural hearing loss of putative genetic origin, and who were negative or heterozygote for the 35delG mutation. Methods: Observational study that analyzed 100 ethnically characterized Brazilian patients with nonsyndromic severe to profound sensorineural hearing loss, who were negative or heterozygote for the 35delG mutation. GJB2 mutations were detected by DNA-based sequencing in this population. Participants' ethnicities were identified as Latin European, Non-Latin European, Jewish, Native, Turkish, Afro-American, Asian and Others. Results: Sixteen participants were heterozygote for the 35delG mutation; 14 participants, including three 35delG heterozygote's, had nine different alterations in the GJB2 gene. One variant, p.Ser199Glnfs*9, detected in two participants, was previously unreported. Three variants were pathogenic (p.Trp172*, p.Val167Met, and p.Arg75Trp), two were non-pathogenic (p.Val27Ile and p.Ile196Thr), and three variants were indeterminate (p.Met34Thr, p.Arg127Leu, and p.Lys168Arg). Three cases of compound heterozygosity were detected: p.[(Gly12Valfs*2)];[(Trp172*)], p.[(Gly12Valfs*2)](;)[(Met34Thr)], and p.[(Gly12Valfs*2)(;)[(Ser199Glnfs*9)]). Conclusion: This study detected previously unclassified variants and one case of previously unreported compound heterozygosity.